4-H Newspaper Supplement Is Model of Volunteer-Business Cooperation; and, Library Tapes Another Outreach Method for Extension - Paul E. Maynard (Journal of Applied Communications, 1984)
4-H Newspaper Supplement: When a large volunteer group such as 4-H wants to get its message across to the community, the best place to look for help may be only as far as the local daily newspaper. Library Tapes: When the Washoe County Extension Office wanted to find a way to work with an expanded clientele, use video production time more efficiently, and find a cooperative venture with another government agency, they looked only as far as the local public library.